Ferdy Sambo Trial News on TvOne-News’s Youtube Account: Critical Discourse Analysis of Police Image in Virtual Public Conversation - Listiyani, Feni; Suryaningtyas, Annis Azhar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Based on Law No. 2 of 2002, it is stated that the Indonesian Police have four strategic roles: law enforcement, protection, service, and community guidance. Unfortunately, in the past four years, there have been numerous violations committed by unethical police officers. The latest data for the period of January-October 2021 shows 1,694 disciplinary violations, 803 violations of the professional code of ethics and the police ethics commission, and 147 criminal violations. This situation was further exacerbated by the murder of Brigadier Nofriansyah Yosua Hutabarat by former Head of Propam, Inspector General Ferdy Sambo. As a result, the police institution has drawn significant attention from various parties, including the media and the public. The news related to this case became headline news in mass media, including TvOneNews. The television station broadcasted Ferdy Sambo's trial on its YouTube channel, sparking discussions among the virtual public. Based on the explanation, this phenomenon becomes interesting to study in-depth, particularly the discourses constructed by netizens regarding the police institution in the news coverage of the trial of the murder case of Brigadier Nofriansyah Yosua Hutabarat with suspect Inspector General Ferdy Sambo, as broadcasted on the TvOneNews YouTube channel. This research adopts the critical discourse analysis method developed by Teun A. Van Dijk. The data collection technique utilizes documentation from the TvOneNews YouTube account. In conclusion, three discourses can be identified from the coverage of Ferdy Sambo's trial on TvOne. Firstly, TvOne aims to establish the reality of Ferdy Sambo's case by featuring the trial in its breaking news program and broadcasting it live on YouTube. Secondly, there is evidence of abuse of authority and power by senior police officers. Lastly, there are indications of improvements in the legal process in Indonesia, which is exemplified by the transparency of Ferdy Sambo's trial through TvOne's live broadcast.